Pengembangan LKPD Mengidenfitikasi Karakteristik dan Unsur Puisi Kelas VII SMP Negeri 32 Bandar Lampung - Putu Ayu Lestari; Fransisca S.O. Dedi; Tri Riya Anggraini (LPPM STKIP PGRI Bandar Lampung, 2020)
This study aims to develop teaching materials products that are effectively used by class VII students. The teaching materials that will be developed are teaching materials in the form of LKPD, namely identifying the characteristics and elements of poetry. This study uses research and development methods by adapting the Jolly and Bolitho development model. To obtain information on the feasibility of teaching materials, expert validation and limited field tests were carried out.. The data obtained to see the potential effects were obtained through analytical tests. Based on the analysis of the results of expert validation, the LKPD teaching materials identified the characteristics and elements of the poetry developed that could be categorized as good or decent. The results of the writing test before and after using the LKPD increased the average score from 68.53 to 87.07 (difference 18.53). Thus, LKPD teaching materials to identify the characteristics and elements of poetry developed can improve students' ability to identify and are suitable for use in SMP Negeri 32 Bandar Lampung.